Influence of Phase Composition on Stress-Corrosion Cracking of Ti-6Mo-5V-3Al-2Fe-2Zr Alloy in 3.5% NaCl Solution - Haoyu Zhang; Jie Sun; Ge Zhou; Xiaoling Yu; Chuan Wang; Jian Gao (Crystals, 2022)
The metastable β titanium alloys used in marine engineering applications suffered from stress-corrosion cracking in seawater. The different phase composition leads to the distinct stress-corrosion cracking behaviors of the alloy. In this work, the influence of the phase composition on the stress-corrosion cracking of a novel metastable β titanium alloy Ti-6Mo-5V-3Al-2Fe-2Zr was investigated. The alloys with different phase compositions were prepared by three types of thermal-mechanical processing, i.e., the single β phase (assigned as M(β)), the β phase plus fine α phase (assigned as M(β+fα)), and the β phase plus coarsened α phase (assigned as M(β+cα)). The electrochemical tests and constant-stress loading tests were performed, and the phase composition and microstructure were analyzed by XRD and SEM. The M(β) alloy exhibits the best corrosion resistance as well as the compact properties of oxide films, followed by the M(β+fα) alloy and the M(β+cα) alloy. Tear ridges and a flat facet with an undulating surface were observed on the stress-corrosion cracking fracture surface, which indicated the occurrence of high-degree dislocations movement and localized plastic deformation. Absorption-induced dislocation emission (AIDE) and hydrogen-enhanced localized plasticity (HELP) are the primary mechanisms for the stress-corrosion cracking of the alloy. The increased amount of β phase has a beneficial effect on stress-corrosion cracking resistance. For the alloy with β and α phases, the α phase with wider spacing has an adverse effect on stress corrosion performance.